MENANGKAL ISLAMOFOBIA MELALUI RE-INTERPRETASI ALQUR’AN - Abdul Aziz (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2016)
Islamophobia has been known as one of the contemporary issues which really raise concerns. It is not a new case indeed, however when it is not taken seriously in an attempt to solve it, it can give negative effect to people’s life, not only for the Muslim, but also for the non-Muslims. This article tries to offer solution through the holy Qur’an’s re-interpretation. Based on the socio-historical approach, by using thematic interpretation, by first collecting some of the Qur’anic’s sentences related to the de-islamophobia then interpreted in accordance with asbâb al-nuzûl and its socio-historical setting followed by the Mufassir’s understanding which is contextualized with today’s context. Since the holy Qur’an has emphasized that Islam is not like what has been believed by the followers of the islamophobia. Islam highly upholds tolerance and peace.